Vehicle Trends in Road Traffic Accidents in Kathmandu Valley - Raut, Rekha; Bohara, Pradeep Kumar; Katuwal, Khadga Bahadur; Basnet, Kirti Bhushan (International Research Journal of MMC, 2026)
Background: Hasty and unplanned urbanization and motorcycle proliferation have turned the Kathmandu valley into a high-friction urban environment. Although the world is trying its best to minimize road traffic injuries (RTIs), the valley still records an increasing trend in road traffic accidents (RTAs), which surpass local infrastructural and regulatory capabilities. Objectives: The main purpose of this research work is to conduct a longitudinal study on road traffic accident (RTA) in the Kathmandu Valley within a span of a twelve-year period (FY 2069/70 to 2081/82). Methods: The research was based on a large sample of over 76 000 instances retrieved with Metropolitan Traffic Police Division (MTPD) to classify the disaggregation of vehicle type, including the Powered Two-Wheelers (PTWs), Light Vehicles, Public Transport and Heavy Goods Vehicles (HGVs). The longitudinal, retrospective empirical design was used in this study. Haddon Matrix and the Safe System Approach are used to analyze systemic failures in the analysis, and Compound Annual Growth rate (CAGR) and proportion share analysis are the methods of quantifying risk shifts. Findings: Findings indicate a total of 153.6 percent projected rise in total RTAs in the course of the study. The most prevalent parties were the PTWs that are engaged in 71.2 percent of all the incidents which posed a serious vulnerability paradox. At the same time, the HGV engagements increased by 362 percent after 2015 with the reconstruction logistics, which introduced a deadly "kinetic imbalance" in mixed-traffic lanes. The most impressive temporal peak was found between 12:00 PM and 6:00 PM (42.5%), which was due to the Environmental Fatigue. The age group of 16-35 years, was the biggest victim group of 55 percent of the victims, and males die three times as many as females. Conclusion: The Kathmandu Valley is now in the state of the infrastructure safety saturation because it is no longer possible to simply limit increasing rates of injuries with the help of behavioral enforcement. The shift in high-speed fatal crashes to urban injury crisis on large scale requires a paradigm shift to Safe System architecture. Some of the recommendations involve introduction of grade separated freight lanes, special lanes of PTWs and time limits on heavy logistics to alleviate the systemic nature of the current road network, which is demanding.